Eixo intestino-pulmão: efeito do consumo de dieta cetogênica no infiltrado neutrofílico pulmonar e susceptibilidade à COVID-19 - Rodrigues, Gabriele Manamy Baba [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The years 2020 and 2021 have been marked by the emergence of a pandemic caused by the SARS-CoV-2 virus, which causes the COVID-19 disease. Since the discovery of the disease, several advances have been made in order to understand the physiopathogenesis of COVID-19 and today it is known that inflammation is a key component of the severe forms of the disease. During the acute phase of the infection, there is a storm of cytokines such as IL-6, IL-17A, TNF and GM-CSF, associated with the extensive neutrophil recruitment found in necropsies of lung tissue in patients who died from the disease. In addition to factors associated with advanced age, several comorbidities have been associated with mortality from COVID-19, in particular diseases that promote increased expression of the angiotensin-converting enzyme (ACE2), which functions as a receptor for the entry of the virus. However, the reason for the high death rate due to COVID-19 in patients with other comorbidities, such as diabetes and obesity, is still unknown. The virus effectively infects the epithelium of the lung and intestinal mucosa and can reach organs such as the kidneys, liver and even the brain. In the Mucosal Immunology Laboratory ICB/USP, we studied how the components of the immune system associated with different mucosal tissues communicate with each other, in particular the intestine-lung axis, and elaborate responses to infections, changes in the composition of the microbiota and dietary changes. In this project, we evaluated whether the consumption of a ketogenic diet (used widely by diabetics and also by individuals with obesity) could influence pulmonary immune homeostasis and, consequently, the outcome of COVID-19. Our results show that the treatment with the ketogenic diet reduced the weight gain and the blood glycemia of the animals, as well as increased the production of ketone bodies. We also found a significant increase in the recruitment of neutrophils and IL-17-producing Tγδ lymphocytes to the vascular compartment of the lung, but not to the tissue parenchyma. Neutrophil recruitment was dependent on IL-17 production. To verify whether such changes could induce a functional impact on pulmonary immunity, we challenged the animals with SARS-CoV-2 and found that diet treatment led to the development of a more severe form of COVD-19 with a mortality rate of 50% and an increase in mononuclear and neutrophilic inflammation in the lung parenchyma. In conclusion, treatment with the ketogenic diet influenced pulmonary immunity and worsened immunopathology due to SARS-CoV-2 infection.

Os anos de 2020 e 2021 têm sido marcados pela emergência de uma pandemia causada pelo vírus SARS-CoV-2, causador da doença COVID-19. Desde a descoberta da doença, vários avanços foram feitos no sentido de se compreender a fisiopatogenia da COVID-19 e hoje sabe-se que a inflamação é um componente chave para as formas graves da doença. Durante a fase aguda da infecção ocorre uma tempestade de citocinas como IL-6, IL-17A, TNF e GM-CSF, associadas ao extenso recrutamento inflamatório, particularmente neutrofílico, encontrado em necropsias de tecido pulmonar de pacientes que vieram a óbito em decorrência da doença. Além de fatores associados à idade avançada, gestação e diversas comorbidades têm sido associadas à mortalidade por COVID -19, em particular a hipertensão, obesidade e o diabetes. Entretanto, não se sabe ainda a razão da alta taxa de morte por COVID-19 nestes grupos de pacientes, particularmente nos pacientes com diabetes e obesidade. No laboratório de Imunologia de Mucosas ICB/USP, estudamos como os componentes do sistema imunológico associado aos diferentes tecidos de mucosa comunicam-se entre si, em particular o eixo intestino-pulmão, e elaboram respostas diante de infecções, alterações na composição da microbiota e alterações na dieta. Neste projeto, avaliamos se o consumo de dieta cetogênica (utilizada amplamente por diabéticos e também por parte de indivíduos com obesidade) poderia influenciar na homeostase imunológica pulmonar e, consequentemente, no desfecho da COVID-19. Nossos resultados mostram que o tratamento com a dieta cetogênica levou a uma redução no ganho de peso dos animais, acompanhada de diminuição da glicemia dos animais e aumento da produção de corpos cetônicos. Encontramos também um aumento significativo no recrutamento de neutrófilos e de linfócitos Tγδ produtores de IL-17 para o compartimento vascular do pulmão, mas não para o parênquima tecidual. O recrutamento dos neutrófilos foi dependente da produção de IL-17. Para verificar se tais alterações poderiam induzir um impacto funcional na imunidade pulmonar, desafiamos os animais com SARS-CoV-2 e verificamos que o tratamento com dieta levou ao desenvolvimento de uma forma mais grave de COVD-19 com mortalidade de 50% e aumento de inflamação mononuclear e neutrofílica no parênquima pulmonar. Em conclusão, o tratamento com a dieta cetogênica influenciou a imunidade pulmonar e agravou a imunopatologia decorrente da infecção por SARS-CoV-2. Acreditamos que a dieta cetogênica pode ser um dos fatores de risco para doença grave em indivíduos diabéticos ou obesos que fazem consumo deste tipo de alimentação.
Gut-lung axis: effect of ketogenic diet consumption on pulmonary neutrophilic infiltrate and susceptibility to COVID-19
Keywords: Infection; Gut-lung axis; Diet; Inflammation; Imunologia; Dieta de baixo carboidrato; Infecção; COVID-19; Mucosa